Penedo Do Gato Rock Art Shelter (Monterrei, NW Iberian Peninsula): In Situ and Laboratory Characterisation - José S. Pozo-Antonio; Beatriz P. Comendador-Rey; Lucía Rodríguez-Álvarez; Pablo Barreiro; Daniel J. Jiménez-Desmond (Heritage)
This paper focuses on the study of the prehistoric art site at Penedo do Gato Rock Art Shelter (NW Spain) through an interdisciplinary collaboration. A key objective was to develop and implement a multi-analytical protocol for characterising prehistoric rock paintings with portable analytical techniques such as colour spectrophotometry and Raman spectroscopy. Additionally, three possible colouring materials collected during the archaeological survey of the site were investigated by means of X-ray diffraction, stereomicroscopy, and scanning electron microscopy (surface and cross-section modes) with the aim of determining their mineralogical composition and texture. The results indicate that hematite (α-Fe2O3) is the main component of the red motifs. Amorphous carbon has been found in several motifs. The presence of amorphous carbon on the rock suggests it may have been deposited onto the paintings by nearby bonfires; however, the potential use of charcoal as an additive in the red pigments to modify their colour should not be overlooked. Regarding the mineralogical composition of potential colouring materials, only one of the samples can be considered as a viable source. This was the only sample with a compact and homogeneous composition, rich in hematite, making it likely that, after grinding, it was used for painting. In contrast, the other collected samples either lacked hematite or contained only a thin layer of it. In these cases, it is unlikely that the hematite layer was extracted using tools to obtain the pigment.